2015
DOI: 10.1007/s10534-015-9828-x
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of ternary oxovanadium(IV) complexes with oxydiacetate and 1,10-phenanthroline or 2,2′-bipyridine. Cytoprotective activity in hippocampal neuronal HT22 cells

Abstract: The aim of this work was to find a relationship between physicochemical properties of the oxovanadium(IV) complexes, namely [VO(ODA)(H2O)2], [VO(ODA)(phen)]·1.5H2O and [VO(ODA)(bipy)]·2H2O (ODA = oxydiacetate) as well as [VO(H2O)5](2+), and their biological activity. A potentiometric titration method has been used to characterize the stability of the complexes in aqueous solutions. Furthermore, the reactivity of the complexes towards superoxide free radicals was assessed by employing the NBT assay as well as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Comparing the stability of VO(ODA)bipy and VO(IDA)bipy complexes it can be concluded that the complex containing IDA ligand is more stable in aqueous solutions than the VO(ODA)bipy complex [27]. This behavior can be explained in terms of the basicity of the primary ligands that is slightly higher for IDA ligand.…”
Section: The Stability Of Vo(ida)bipy In Aqueous Solutionsmentioning
confidence: 91%
See 4 more Smart Citations
“…Comparing the stability of VO(ODA)bipy and VO(IDA)bipy complexes it can be concluded that the complex containing IDA ligand is more stable in aqueous solutions than the VO(ODA)bipy complex [27]. This behavior can be explained in terms of the basicity of the primary ligands that is slightly higher for IDA ligand.…”
Section: The Stability Of Vo(ida)bipy In Aqueous Solutionsmentioning
confidence: 91%
“…All solutions used to measurements were degased with argon. The oxygen concentration in the measured solution was in the 1.5-2.2Á10 À3 mol/L range [12,[24][25][26][27].…”
Section: The Cyclic Voltammetry (Cv)mentioning
confidence: 99%
See 3 more Smart Citations